Effect of numerous plate holes in a cooling tower on heat transfer optimization - Suansyah, Heli; Syuhada, Ahmad; Sofyan, Sarwo Edhy (Jurnal Polimesin, 2023)
An industry requires a cooling medium to reduce heat in an industrial machine during operation. Companies generally use cooling towers for engine cooling media. The common issue is that heat reduction and heat transfer rate are not significant. Therefore, a new variation is needed to ensure that the cooling tower can effectively lower the temperature of the machinery. The problem statement aims to determine the parameters that can enhance both the heat transfer rate and the heat transfer coefficient in cooling towers. The objective is to determine the heat transfer rate and heat transfer coefficient. The method used is experimental by varying the water inlet in five variations of the cooling tower plates, they are being 48, 60, 80, 120, and 250 holes. The results showed that the highest temperature difference occurs at Tin 80oC with the variation of 250 holes, which is 9.34oC, and the highest heat transfer value reached 1833.17 watts. Meanwhile, the lowest temperature difference occurred at Tin 60oC with a variation of 48 holes, which is 3,98oC, and the lowest heat transfer value reached 787.47 watts. The highest convection coefficient occurs at Tin 70oC with the variation of 250 holes, which is 117.74 W/m²⋅K. The lowest convection coefficient occurs at Tin 80oC with a variation of 48 holes, which is 77.36 W/m²⋅K. This can be concluded that the temperature difference (⧍T), heat transfer rate, and heat transfer coefficient will increase when the number of holes in each plate variation increases.